Good Corporate Governance Principles and Performance of Local Finance Institutions - Suryandari, Ni Nyoman Ayu; Wangi, Ni Luh Ayu Sekar; Oktaviani, Ni Kadek; Trisnayuni, Komang Ayu Sintha (Journal of International Conference Proceedings, 2024)
The purpose of this research is to find empirical results on the influence of GCG principles on the performance of local finance institutions in Bali. The local finance institution in Bali is popular called Lembaga Perkreditan Desa (LPD). The GCG principles used in this study are transparency, accountability, responsibility, independence, and fairness. The population in this study was 557 employees. There are 102 respondents collected using the purposive sampling method which consists of the head of LPD, the head of the supervisory board, and the head of the accounting of each LPD in Denpasar. The data analysis technique used is multiple linear regression analysis. The research results show that independence positively influences the performance of LPD. In contrast, transparency, accountability, responsibility, and fairness do not affect LPD performance. The LPD’s management has an important role in increasing the principle of independence because independence has the most dominant influence on the performance of LPD in Denpasar.